Tuanku Nan Renceh : Pengaruh dan Warisan Nya dalam Sejarah Minangkabau - Muhammad Fharel Rafer Perdana; Merdiana L. Sipahutar; Iga Putri Pamungkas; Hera Hestuti; Aisiah Aisiah (Mandub : Jurnal Politik, Sosial, Hukum dan Humaniora, 2025)
Tuanku Nan Renceh is an important figure in the history of Islam in Minangkabau who is known as a pioneer of the religious reform movement through the Padri Movement. Born into a strong matrilineal customary environment, he became a symbol of the radical transformation of Islamic thought in Indonesia in the 19th century. Starting from traditional education in the surau to being inspired by the Wahabi teachings brought by three pilgrims from Mecca, Tuanku Nan Renceh became the driving force behind the purification of Islam that rejected all forms of heresy, superstition, and customary practices that were considered contrary to Islamic law. His leadership was not only spiritual but also military in its resistance against customary groups and Dutch colonial power. His intellectual legacy influenced modern reformist movements such as Muhammadiyah and gave birth to local philosophies such as "Adat Basandi Syarak, Syarak Basandi Kitabullah". Although his preaching method is considered controversial because it prioritizes violence and confrontation, Tuanku Nan Renceh's role remains significant in the dialectic of Islam and Minangkabau customs. Historical narratives, popular culture, and the collective memory of society immortalize his figure as a fighter, reformer, and symbol of the conflict between Islamic orthodoxy and local wisdom. This article will discuss again how Tuanku Nan Renceh's role in Spreading Influence played a major role in Minangkabau history, and invite readers to recognize, understand, and respond to the valuable legacy left behind.